Prognostic analysis of radical resection for iCCAphl and iCCApps: A retrospective cohort study - Yu, Zetao; Ni, Qingqiang; Jia, Hongtao; Gao, Hengjun; Yang, Faji; Zhu, Huaqiang; Liu, Fangfeng; Wang, Jianlu; Zhou, Xu; Chang, Hong; Lu, Jun (Frontiers in Oncology, 2022)
Backgroud At present, there is no definitive conclusion about the relative prognostic factors on intrahepatic cholangiocarcinoma perihilar large duct type (iCCAphl) and iCCA peripheral small duct type (iCCApps). Aim of the study To compare the prognoses of two different types of iCCA, and identify the independent risk factors affecting the long-term survival of patients undergoing radical resection for iCCA. Methods This study included 89 patients with iCCA who underwent radical resection at the Department of Hepatobiliary Surgery of the East Yard of the Shandong Provincial Hospital between January 2013 and March 2022. According to the tumor origin, these patients were divided into the iCCAphl group (n = 37) and iCCApps group (n = 52). The prognoses of the two groups were compared using Kaplan–Meier analysis, whereas the independent risk factors of their prognoses were identified using Cox univariate and multivariate regression analyses. Results In the iCCApps group, the independent risk factors for overall survival included diabetes history (p = 0.006), lymph node metastasis (p = 0.040), and preoperative carbohydrate antigen 19-9 (p = 0.035). In the iCCAphl group, the independent risk factors for overall survival included multiple tumors (p = 0.010), tumor differentiation grade (p = 0.008), and preoperative jaundice (p = 0.009). Conclusions Among the iCCA patients who underwent radical resection, the long-term prognosis of iCCApps maybe better than that of iCCAphl. The prognoses of these two types of iCCA were affected by different independent risk factors.